The Visitor Journey Analysis of Tourists in Garut Regency - Maspupah, Dini (Politeknik Negeri Bandung, 2023)
Garut Regency has great tourism potential with increasing visits, but there needs to be more information regarding tourists' journeys during their visit. This study aims to understand the journey of tourists before, during, and after visiting Garut Regency using the visitor journey variables in five phases (dreaming, planning, booking, experience, and sharing). The method used is quantitative research with a descriptive statistical approach, using a questionnaire as the research instrument. Most tourists who have visited Garut Regency in the past year are female Gen Z students from West Java, with few tourists from outside West Java. In the Dreaming phase, they plan to travel to other provinces, especially beaches, using private vehicles with their families. In the Planning phase, tourists pay attention to affordable prices, unique and beautiful nature, and local cuisine. Instagram social media serves as the primary source of information. In the Booking phase, tourists are interested in attractive destination photos and prefer offline ticket bookings rather than through OTA. In the Experience phase, tourists are motivated to visit with an average of more than four visits and expenses below IDR 1 million. Natural tourism has become the main image of Garut Regency. In the Sharing phase, most tourists share their experiences through Instagram social media after visiting Garut Regency.